Macroline, talpinine, and sarpagine alkaloids from Alstonia penangiana. An NMR-based method for differentiating between A. penangiana and A. macrophylla - Yeap, Joanne Soon Yee; Tan, Chun Hoe; Yong, Kien Thai; Lim, Kuan Hon; Lim, Siew Huah; Low, Yun Yee; Kam, Toh Seok (Elsevier, 2020)
Fourteen previously undescribed alkaloids comprising two N-1-hydroxymethylmacroline alkaloids, one talpinine-type oxindole acetal, a pair of equilibrating talpinine-type oxindole hemiacetals, eight oxidized derivatives of sarpagine- and akuammiline-type indole alkaloids, in addition to alstochalotine a diastereomer of gelsochalotine recently isolated from Gelsemium elegans, were isolated from the leaf and stem-bark extracts of Alstonia penangiana. The structures and relative configurations of these alkaloids were established using NMR, MS, and in one instance, confirmed by X-ray diffraction analysis. An NMR-based method is described as a useful chemotaxonomic tool for differentiating between A. penangiana and A. macrophylla. Several of the alkaloids isolated showed appreciable growth inhibitory effects when tested against a number of human cancer cell lines. © 2020 Elsevier Ltd